STRATEGI PRODUK INDIVIDU, LINI PRODUK, DAN BAURAN PRODUK - Abdul Wahab Syakhrani; Akhmad Latif, Fahrul (JOURNAL OF COMMUNITY DEDICATION, 2023)
Product strategy is one of the important aspects of marketing which is related to the development, management and marketing of products or services. This article discusses product strategy in three main dimensions: individual product strategy, product line, and product mix. Individual product strategy is concerned with the development, planning, and marketing of a single product. In this context, companies must consider aspects such as pricing, product positioning in the market, design, branding and marketing communications. The success of these individual products is critical to the company's overall product portfolio. In addition, a product line is a collection of products offered by a company in a particular category or market. Product line strategy involves managing a product portfolio to cover various market segments and maximize company profits. This includes developing new products, discontinuing less successful products, and adjusting prices and product attributes. Product mix, on the other hand, includes all the elements that influence customer perception of the product, such as design, quality, brand, and price. Companies must consider how to best integrate these elements to create added value for customers and differentiate their products from competitors. In an era of increasing competition, a good understanding of individual product strategies, product lines and product mix is essential. Companies need to continuously monitor the market, consumer trends, and competitor behavior to develop effective product strategies. By combining these elements well, companies can maximize market share, increase profits, and better meet customer needs.